APPLICATION OF THE ARIMA MODEL FOR PREDICTION OF MONTHLY DIVORCE RATE IN THE RELIGIOUS COURTS IN SOUTH SUMATRA - Fitriati, Sri; Rini, Dian Palupi; -, Firdaus (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2024)
This research discusses predictions of divorce rates in Religious Courts in South Sumatra. This is important to do because the divorce rate has a changing trend. Sometimes high and sometimes low but always at a high trend number, so soCourt officials or social scientists in developing effective strategies for overcoming marriage problems, allocating resources, or supporting families who need counseling can be prepared in advance, especially at the Religious Courts in South Sumatra to reduce the divorce rate because the purpose of marriage is not to divorce. This research discusses the divorce rate in terms of predicting/forecasting because much research has been done on the divorce rate by examining the causes of divorce. This research uses the ARIMA (Autoregressive Integrated Moving Average) model to predict. The ARIMA model is a method that has been widely used in forecasting research to get good results. The research results are that the ARIMA model used is (1,0,2) and (2,0,2), with an error rate of only 0.48% using the MAPE method. Keywords: predictions, numbers, divorce, arima, mape.